2014
DOI: 10.1074/jbc.m114.597732
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Glucuronoxylan-specific Xyn30D and Its Attached CBM35 Domain Gives Insights into the Role of Modularity in Specificity*

Abstract: Background: Xylanases are crucial in plant cell wall recycling. Results: A glucuronoxylan-specific xylanase is attached to its binding module with moderate flexibility. This CBM35 displays novel structural features regulating specificity. Conclusion: Depolymerization of highly substituted xylans and an oriented interaction with its target substrate are proposed. Significance: Unraveling the mechanisms ruling modularity is essential to understanding the biomass deconstruction and to producing efficient biocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…They generally differ from the endoxylanases in family 10 by having high selectivity for glucuronoxylan and XOS substituted with glucuronic acid (GlcA) or methylglucuronic acid (MeGlcA) via an α-1,2 linkage. This is combined with lower selectivity for unsubstituted xylan, AX, and XOS, which may be structurally reflected by more open-binding clefts (Sainz-Polo et al 2014 ). (At least one exception from this rule is however known as the enzyme from C. papyrosolvens (St John et al 2014 ) is active on non-substituted xylan).…”
Section: Gh30 Glucuronoarabinoxylan Endoxylanasesmentioning
confidence: 99%
See 1 more Smart Citation
“…They generally differ from the endoxylanases in family 10 by having high selectivity for glucuronoxylan and XOS substituted with glucuronic acid (GlcA) or methylglucuronic acid (MeGlcA) via an α-1,2 linkage. This is combined with lower selectivity for unsubstituted xylan, AX, and XOS, which may be structurally reflected by more open-binding clefts (Sainz-Polo et al 2014 ). (At least one exception from this rule is however known as the enzyme from C. papyrosolvens (St John et al 2014 ) is active on non-substituted xylan).…”
Section: Gh30 Glucuronoarabinoxylan Endoxylanasesmentioning
confidence: 99%
“…Other enzymes are shown to be connected to a CBM, e.g. CBM35 of Xyn30D from Paenibacillus barcinonensis (Sainz-Polo et al 2014 ) that is reported to be glucuronoxylan binding. Overall, GH30_8 candidates differ in modularity, some enzymes being single module, while others are connected to binding modules or parts of cellulosomes.…”
Section: Gh30 Glucuronoarabinoxylan Endoxylanasesmentioning
confidence: 99%
“…Here, we determined the structure of CtXyn30A in its native form and that of the CtXyn30A-E225A mutant bound to xylotetraose. Comparison of the GH30 structure with those of XynA from E. chrysanthemi (Urbá niková et al, 2011), XynC from B. subtilis (St John et al, 2011), CpC71 from C. papyrosolvens (St John et al, 2014) and XynD from P. barcinonensis (Sainz-Polo et al, 2014) revealed remarkable conservation in the catalytic machinery of both mesophilic and thermophilic glucuronoxylan endo--1,4-xylanases.…”
Section: Introductionmentioning
confidence: 99%
“…Paenibacillus barcinonensis BP-23 is a powerful xylanolytic bacterial strain isolated from rice field soil (15) that produces a complex secretome, including different xylanases from families GH10, GH11, and GH30 that have already been cloned and characterized (16)(17)(18)(19). Some of these enzymes have been successfully evaluated in industrial applications (20,21).…”
Section: Importancementioning
confidence: 99%